1976
DOI: 10.1021/bi00671a007
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular proton nuclear Overhauser effect study of the solution conformation of valinomycin in dimethyl sulfoxide

Abstract: Determination of the mechanism of intramolecular nuclear Overhauser effects (NOE) in peptides and depsipeptides is essential to the use of this technique in conformational analysis of these and related biomolecules. Towards this end, 1H NMR double-resonance studies were conducted on valinomycin in (CD3)2SO at 90 MGZ (FT mode) and 250 MGZ (correlation mode). The NOE's are positive at the lower frequency and negative at the higher frequency. Consideration of the theoretical dependence of the NOE on the proton-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Stern, Gibbons & Craig, 1968;Ovchinnikov et al 1970;Urry & Ohnishi, 1974;Wiithrich, Grathwohl & Schwyzer, 1974;Kopple, Go & Pilipauskas, 1975;Howard et al 1975;Stimson, Zimmerman & Scheraga, 1977). Recently, the applicability of the technique has been extended by use of the nuclear Overhauser effect to distinguish between various types of bend conformations (Khaled & Urry, 1976) and, in general, to obtain information about the dihedral angle ijr, for rotation about the C a -C bond, and about side-chain conformation (Glickson et al 1976;Leach, Nemethy & Scheraga, 1977). However, the application of NMR to the study of globular proteins is much more difficult because of overlapping of the resonances from the many protons of the protein molecule.…”
Section: The Exposure Of Residues To the Solventmentioning
confidence: 99%
“…Stern, Gibbons & Craig, 1968;Ovchinnikov et al 1970;Urry & Ohnishi, 1974;Wiithrich, Grathwohl & Schwyzer, 1974;Kopple, Go & Pilipauskas, 1975;Howard et al 1975;Stimson, Zimmerman & Scheraga, 1977). Recently, the applicability of the technique has been extended by use of the nuclear Overhauser effect to distinguish between various types of bend conformations (Khaled & Urry, 1976) and, in general, to obtain information about the dihedral angle ijr, for rotation about the C a -C bond, and about side-chain conformation (Glickson et al 1976;Leach, Nemethy & Scheraga, 1977). However, the application of NMR to the study of globular proteins is much more difficult because of overlapping of the resonances from the many protons of the protein molecule.…”
Section: The Exposure Of Residues To the Solventmentioning
confidence: 99%
“…Most of the solution proton ( 1 H) NMR studies of drug-membrane interactions utilize detergent micelles or organic solvents instead of bilayer membranes (22,23). However, the packing of phospholipids in micelles is remarkably different from that in a bilayer (24).…”
mentioning
confidence: 99%
“…These factors have meant that scalar relaxation effects have been considered unlikely to be apparent in NOE experiments performed with modern high-field spectrometers. [16] We believe scalar cross-relaxation of the first kind has not previously been reported as being observed in 2D NOESY spectra and, it appears, the effect has only rarely been detected experimentally. The clearest example of this appears to be the work of Fukumi et al [17] over forty years ago in which negative NOEs were observed between the coupled CH-OH protons of methanol and ethanol and attributed to scalar relaxation.…”
mentioning
confidence: 76%